Mass spectrometry study of plant steroid glycosides and their interactions with biomolecules - Pilipenko, V.V.; Sukhodub, L.F. (Біополімери і клітина, 2002)
A number of plant steroid glycosides (SGs) and genins nave been investigated by ²⁵²Cf plasma desorption mass spectrometry (²⁵²Cf TOF-PDMS). PDMS was also applied for comparative studies of the interactions of SGs and their genins with basic amino acids, nucleosides and AMP. SGs can interact with these biomolecules to form heteroclusters of the types [SG + biomolecule + H]+ and [SG + biomolecule + K]+, the affinity of SGs for biomolecules depends on the structures of the SG carbohydrate chain and the SG aglycone, and the biomolecule nature.